2017
DOI: 10.1002/prop.201700038
|View full text |Cite
|
Sign up to set email alerts
|

Quantum‐corrected Geometry of Horizon Vicinity

Abstract: We study the deformation of the horizon-vicinity geometry caused by quantum gravitational effects. Departure from the semi-classical picture is noted, and the fact that the matter part of the action comes at a higher order in Newton's constant than does the Einstein-Hilbert term is crucial for the departure. The analysis leads to a Firewalltype energy measured by an infalling observer for which quantum generation of the cosmological constant is critical. The analysis seems to suggest that the Firewall should b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 74 publications
1
39
0
Order By: Relevance
“…The analysis consists of three components: computation of the quantum action (for which we referred to the previous works) and its time-dependent solution, computation of the four-velocity of the observer, as well as evaluation of the energy after expansion around the location of the horizon. As in the previous works [6] [7], a trans-Planckian energy has resulted. Concerning the physical origin of the trans-Planckian energy behavior, the loop effects become important near the horizon.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…The analysis consists of three components: computation of the quantum action (for which we referred to the previous works) and its time-dependent solution, computation of the four-velocity of the observer, as well as evaluation of the energy after expansion around the location of the horizon. As in the previous works [6] [7], a trans-Planckian energy has resulted. Concerning the physical origin of the trans-Planckian energy behavior, the loop effects become important near the horizon.…”
Section: Resultsmentioning
confidence: 62%
“…Such effects may be behind some of the highly energetic astrophysical phenomena. In the previous works [6] [7], we considered an Einstein-scalar system and examined the possibility that the quantum corrections may produce a violent energy behavior in the vicinity of the event horizon. It was shown that for a time-dependent solution, one indeed encounters such a behavior.…”
Section: Time-dependent Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this there may again be "order-1" modifications to the classical picture. In [92] and [93] (see an earlier related work [94]), the energy measured by an infalling observer was studied for two different cases: quantum-corrected time-dependent dS-Schwarzschild and AdS black holes. It turns out that the infalling observer encounters a trans-Planckian energy near the horizon of the black hole, which is consistent with the Firewall proposal [95] [96].…”
Section: Beta Function Analysismentioning
confidence: 99%